2006
DOI: 10.1029/2005wr004009
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation water demand: A meta‐analysis of price elasticities

Abstract: [1] Metaregression models are estimated to investigate sources of variation in empirical estimates of the price elasticity of irrigation water demand. Elasticity estimates are drawn from 24 studies reported in the United States since 1963, including mathematical programming, field experiments, and econometric studies. The mean price elasticity is 0.48. Long-run elasticities, those that are most useful for policy purposes, are likely larger than the mean estimate. Empirical results suggest that estimates may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(88 citation statements)
references
References 26 publications
8
74
1
5
Order By: Relevance
“…The potential of meta-analysis in identifying the sources of variation in empirical value estimates (Johnston et al 2003;Scheierling et al 2006) and as a tool for value transfer (Bergstrom and Taylor 2006; is generally acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of meta-analysis in identifying the sources of variation in empirical value estimates (Johnston et al 2003;Scheierling et al 2006) and as a tool for value transfer (Bergstrom and Taylor 2006; is generally acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…O Gráfico 3 mostra as curvas de demanda dos municí-pios com atividade agrícola significativa no submédio do São Francisco. Para a demanda de água para irrigação difusa, foi aplicada elasticidade-preço igual a 0,48 (SCHEIERLING et al, 2006).…”
Section: Nilo Coelhounclassified
“…A elasticidade-preço da demanda é uma medida econômica usada muitas vezes para avaliar a eficá-cia de um sistema de preços, no sentido de incentivar a conservação de água ou a viabilidade econômica de transferir água de um uso para outros. Os formuladores de políticas interessados em estimar os efeitos das modificações em preços dos recursos hídricos podem basear-se em estimativas da elasticidade-preço da demanda (SCHEIERLING et al, 2006).…”
unclassified
“…It has been indicated in many studies that there are three thresholds for prices leading to different elasticity in groundwater demand change (Scheierling et al 2004;Varela-Ortega et al 1998;Yang et al 2003). The groundwater can become inelastic at a too low price or at a too high price level.…”
Section: A Theoretical Analysis Using Graphsmentioning
confidence: 99%
“…In the theoretical analysis, the relation between the cost for groundwater and the consumption of rainwater is studied graphically by analysing the elasticity of groundwater. Many studies con-cerned with the price elasticity of irrigation water have found that when the price of water is lower than a threshold, irrigation water is price inelastic (Berbel and Gomez-Limon 2000;Salman and Al-Karablieh 2004;Scheierling et al 2004;Yang et al 2003). The cost for groundwater should be higher than the elasticity threshold so that the consumption of groundwater is sensitive to its cost.…”
Section: Groundwater Charge and Rainwater Consumption For Agriculturamentioning
confidence: 99%